Effect of Nanostructure Morphology and Concentration on the Piezoelectric Performance of Flexible Pressure Sensor based on PVDFTrFE/ Nano-ZnO Composite Thin Film - Liu, Yurong; Zeng, Xiaolong; Zhu, Lin; Wang, Cong; Geng, Kuiwei; Yao, Ruohe (Current Nanoscience, 2024)
Background: The development of high-performance piezoelectric pressure sensors with outstanding sensitivity, good linearity, flexibility, durability, and biocompatibility is of great significance for smart robotics, human healthcare devices, smart sensors, and electronic skin. Thus, considerable progress has been achieved in enhancing the piezoelectric property of PVDF-TrFEbased composite pressure sensors by adding various ZnO nanostructures in PVDF-TrFE polymer acting as a nucleating agent and dielectric material. Aims: In this work, flexible pressure sensors with a sandwich structure based on PVDFTrFE/ nano-ZnO composite sensing film were fabricated using a simple spin-coating method and post-annealing process, while electrospinning and high-voltage polarization processes were not adopted. Methods: Poly (vinylidene fluoride-trifluoroethylene) (PVDF-TrFE)/nano-ZnO composite films were prepared via spin coating to fabricate flexible piezoelectric pressure sensors. ZnO nanoparticles (ZnO NPs), tetrapod ZnO (T-ZnO) and ZnO nanorods (ZnO NRs) were used as nano-fillers for piezoelectric PVDF-TrFE, to enhance the beta-crystal ratio as well as the crystallinity of PVDF-TrFE. The structural and surface morphologies of the composite films were investigated using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results: Among three different types of ZnO nanostructures with a concentration range (0-7.5 wt%), the sensor with 0.75 wt% ZnO NRs nanofiller exhibits a maximum output voltage of 1.73 V under an external pressure of 3 N and a maximum sensitivity of 586.3 mV/N at the range of 0-3 N. Further, the sensor can generate a clear piezoelectric voltage under bending and twisting deformation as well as compression and tensile deformation. Conclusion: To summarize, the addition of different concentrations of nano-ZnO can remarkably improve the piezoelectric performance of the composite sensor, and ZnO NRs can achieve better piezoelectric properties of the sensor as compared to ZnO NPs and T-ZnO. In addition, the sensor with 0.75 wt% ZnO NRs as nanofiller has the highest piezoelectric response, which is about 2.4 times that of the pure PVDF-TrFE sensor. It is demonstrated that the sensor has great potential applications in wearable health monitoring systems and mechanical stress measurement electronics.
Keywords: nano-ZnO